Innovations in tourism - Lysіuk, Tatiana V. (My University, 2022)
It was analyzed which tourist enterprises are the most innovative and, as a result, competitive in the tourist market. An expert-evaluative analysis of the trends in the implementation of innovations by tourism enterprises was carried out, which makes it possible to assert the readiness of the domestic tourism market for the introduction of the latest technologies, such as chatbots, blockchain technologies, artificial intelligence and the Internet of Things. It is argued that the economic situation in the country, the social condition of the population, national legislation, as well as intergovernmental and international agreements affect the implementation of innovations in tourism.
Keywords: tourism; innovations by tourism; tourist market; Ukraine; tourism sector